Roles of leucine-rich alpha-2-glycoprotein 1 in normal and diabetic wound healing - Liu, Chenghao (2019)
Leucine-rich alpha-2-glycoprotein 1 (LRG1) is a novel modulator of TGFβ signaling. This study shows LRG1 expression is increased during wound healing. Lrg1-/- mice show delayed wound healing, altered immune cell infiltration, re-epithelialization, angiogenesis and fibroblast activation in vivo. Cell-based studies reveal that LRG1 differentially regulates TGFβ signaling pathway in keratinocytes, endothelial cells and fibroblasts. Surprisingly, LRG1 expression is significantly increased in ulcers and serum of diabetic foot ulcer patients and wounds from streptozotocin-induced diabetic mice. Under diabetic conditions, deletion of Lrg1 accelerates wound healing in mice. Western blot analysis shows reduced formation of neutrophil extracellular traps in the wounds of diabetic Lrg1-/- mice. Neutrophils isolated from Lrg1-/- mice are less susceptible to inducer of ΝΕΤs formation. Consistently, recombinant LRG1 can induce NETosis in human neutrophils by activating extracellular signal-regulated kinases. Taken together, this study provides new insights into the complex role of LRG1 in normal and diabetic wound healing.